Mental health and substance use among rehabilitation sciences students during the COVID-19 pandemic - Itumeleng Ntatamala; Saajida Khan; Zenzo Chakara (South African Journal of Psychiatry)
Background: An increase in mental health problems have been documented in health sciences students globally during the coronavirus disease 2019 (COVID-19) pandemic.